2003
DOI: 10.14430/arctic625
|View full text |Cite
|
Sign up to set email alerts
|

Local Ecological Knowledge of Ivory Gull Declines in Arctic Canada

Abstract: We gathered local ecological knowledge (LEK) on the ivory gull (Pagophila eburnea) from residents of three High Arctic communities in eastern Canada. This gull has always been uncommon, but Inuit had suggested that numbers of gulls were declining. LEK from Grise Fiord and Resolute Bay was clear and consistent, indicating that far fewer gulls are currently observed near the community compared to 25 years ago. The LEK from Arctic Bay was less consistent, although in general, community members thought that the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 18 publications
(25 reference statements)
6
57
0
1
Order By: Relevance
“…Inuit hunters are providing important observations on these changes that have subsequently been confirmed by scientific surveys (e.g., Robertson and Gilchrist 1998;Mallory et al 2003). While much of our evidence is presently circumstantial, the observations and oral reports documented here lay the baseline for directed surveys to confirm distributional extensions.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Inuit hunters are providing important observations on these changes that have subsequently been confirmed by scientific surveys (e.g., Robertson and Gilchrist 1998;Mallory et al 2003). While much of our evidence is presently circumstantial, the observations and oral reports documented here lay the baseline for directed surveys to confirm distributional extensions.…”
Section: Discussionsupporting
confidence: 63%
“…These results were then summarized and published (Priest and Usher 2004), such that results for a community represent harvest in that year within the hunting region around that area. Other data were also collected as part of local ecological knowledge studies focused on various subjects during discussions with Inuit hunters and Wildlife Resource Officers in communities along Baffin Bay (e.g., Mallory et al 2003). Local knowledge has proven to be an effective means of examining wildlife distributions in the Arctic, as Inuit are keen observers of their environment (Gilchrist et al 2005*).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we showed that the variability in the quantity of mapped observations was explained by the community of residence and average number of hunting 1 3 and changes in whale migratory routes due to movement of the ice pack (Huntington 2000). Further, local knowledge from residents of three high Arctic communities in eastern Canada reported broad population declines of the ivory gull (Pagophila eburnea), an issue previously not fully recognized by the scientific community (Mallory et al 2003). It has become increasingly appreciated by the scientific community that TEK/LEK has enhanced our understanding of the ecology of species, and is valuable for their future management (Service et al 2014;Pardo-de-Santayana and Macía 2015).…”
Section: Introductionmentioning
confidence: 81%
“…Traditional and local ecological knowledge (TEK/ LEK, defined in methods), gathered through interviews with harvesters living in close relationship with wildlife, is a key source of information (Huntington 2011;Pardode-Santayana and Macía 2015). The resulting TEK/LEK qualitative database can provide information on aspects of wildlife ecology, which are not always targeted by the scientific community, or which are beyond the reach of traditional scientific observations, particularly for wide ranging species living in remote environments (Mallory et al 2003;Huntington 2011;Service et al 2014). For example, initial population estimates of 2000-3000 bowhead whales (Balaena mysticetus) obtained from visual coastal counts, increased to 6000-8000 after native Alaskans pointed out the inaccuracy of the census method, which did not take into account diving whales Abstract Traditional and local ecological knowledge (TEK/LEK) are important sources of information for wildlife conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Esto se debe en gran medida, a que pueden existir sesgos asociados al conocimiento de las especies. Por ejemplo, los informadores que no han sido entrenados previamente suelen proporcionar información más fiable de especies carismáticas o fáciles de identificar, como es el caso de los vertebrados grandes y/o peculiares (Mallory et al 2003). En ese sentido, los participantes de nuestro estudio mencionaron frecuentemente dos especies carismáticas de la zona como el puma y el monito de monte, pese a que no suelen alcanzar grandes densidades en bosques templados húmedos del sur de Chile (Iriarte 2008).…”
Section: Discussionunclassified